1987
DOI: 10.1302/0301-620x.69b3.3584189
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival in patients with femoral neck fractures

Abstract: A prospective study of factors which might help to predict mortality in patients with intracapsular fractures of the femoral neck has been undertaken. A multivariate analysis technique was used to analyse the collected data, and it was found that mental ability was the most significant variable; this factor had the greatest effect on outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
2
8

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 0 publications
3
43
2
8
Order By: Relevance
“…Van Balen et al 21 report that 67% of the patients showed two or more associated diseases to femoral fracture, and mortality rates range from 4% for patients with one associated disease, 15% in those with two associated diseases, 26% in those with three, and 47% when four or more concomitant diseases are found. Mortality rate ranges from 14 to 36% according to some authors [22][23][24] . Cunha et al 25 report a rate of 25%.…”
Section: Deathsmentioning
confidence: 99%
“…Van Balen et al 21 report that 67% of the patients showed two or more associated diseases to femoral fracture, and mortality rates range from 4% for patients with one associated disease, 15% in those with two associated diseases, 26% in those with three, and 47% when four or more concomitant diseases are found. Mortality rate ranges from 14 to 36% according to some authors [22][23][24] . Cunha et al 25 report a rate of 25%.…”
Section: Deathsmentioning
confidence: 99%
“…5 High complication and mortality rates associated with hip fractures have been well documented in the literature. [6][7][8][9][10][11][12][13][14][15] Poor outcomes may be predicted by patient comorbidities, surgical timing, and surgical volume. 7,[15][16][17][18][19][20][21][22][23][24][25][26][27] The effect of surgical time of day on hip fracture outcome is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, Parker and Pryor (2000) found that internal fixation and uncemented hemiarthroplasty were equally good in patients over 70 years. The demented patient with a displaced femoral neck fracture poses a special problem because of the higher risk of dislocation of the prosthesis (Khan et al 1981, Woolson andRahimtoola 1999) and higher mortality after a femoral neck fracture (Ions andStevens 1987, Clayer andBauze 1989). van Dortmont et al (2000) considered internal fixation safer in this patient group, since they had a higher mortality after hemiarthroplasty than lucid patients.…”
mentioning
confidence: 96%